The Efficacy of Implementing Labor Analgesia Education via the WeChat Public Platform—A Randomized Controlled Study - Lijun Ma; Yan Cheng; Hailian Liu; Wenjing Yang; Chen Yang (Clinical and Experimental Obstetrics & Gynecology)
Background: Previous research has revealed that utilizing videos or images to educate primiparas about labor analgesia yields significantly superior results. WeChat supports various types of media, making it an ideal carrier for educational content. We have established a WeChat public account where educational content is presented through videos, images, and relevant scientific articles. We will investigate the effectiveness of WeChat public platform in primiparas analgesia education. Methods: Primiparas were randomly assigned to either the WeChat public account education group (W group) or traditional bedside education group (B group). The labor analgesia knowledge questionnaires, self-rating anxiety scales, and the time taken for positioning were compared between the two groups. Additionally, satisfaction with labor analgesia was evaluated post-delivery. Results: A total of 90 primiparas were completed the study. Compared to the B group, primiparas in the W group had higher scores on labor analgesia knowledge questionnaire (55 ± 11.1 vs. 65 ± 9.2, p = 0.001), lower anxiety scores (51.4 ± 5.4 vs. 48.9 ± 4.6, p = 0.02), shorter positioning time (27.5 ± 7.9 s vs. 20.1 ± 9.2 s, p = 0.001) than those in the B group. The satisfaction of anesthesiologists with body positioning and the satisfaction of primiparas with labor analgesia were similar between the two groups. Conclusions: The use of WeChat public platform for labor analgesia education can enhance primiparas understanding and cooperation during the procedure, decreasing maternal anxiety. It also benefits anesthesiologists by improving work efficiency. It has significant clinical value and promising prospects for promotion. Clinical Trial Registration: The study was registered with the Chinese Clinical Trial Registry (ChiCTR1900025231).